Study on the efficiency of the game actions in women's handball World Championship Denmark 2015 - Leuciuc, F. V. (Annals of the University Dunarea de Jos Galati, Fascicle XV: Physical Education and Sport Management, 2016)
The aim of this study is to analyze the efficiency of the game actions in attack and defense of the participating teams and the trends of the game. The teams have played between 6 and 9 games (places 1-8 - 9 games, places 9-16 - 6 games, places 17-24 - 7 games), was played 88 games for the establishment of the final hierarchy. In the final ranking of the competition in the first 12 teams were 11 from Europe and 1 from America, and among the last 12 have 2 from Europe, 4 from Asia, 3 from Africa and 3 from America. In terms of efficiency indicators that are observed in the first part of the ranking teams they perform consistently, but teams ranked in last positions barely manage to perform in one or two of them. The data obtained can be used as benchmarks of efficiency because they are actualy, but should be a study of a longer period of time for the analysis performed to have a high degree of veridicity and data to be used as benchmarks for the following competitions.